A Forgotten Cause of Dyspepsia - Sharma, Brij; Bodh, Vishal; Bhateja, Anshul (Journal of Digestive Endoscopy, 2024)
A 63-year-old female patient presented with complaints of epigastric pain for 2 months associated with postprandial fullness and early satiety. She gave history of open cholecystectomy 2 years back at a peripheral hospital. Her general physical and systemic examinations were within normal limits. Her routine investigations including hemogram, liver and renal biochemistries, and ultrasound abdomen were normal. She had received multiple courses of oral proton pump inhibitors, prokinetics, antacids, and antispasmodics but had no relief. In view of her persistent complaint and age more than 60 years, her esophagogastroduodenoscopy (EGD) was planned. Her EGD revealed deeply embedded large gauze piece in the posterior wall of the first part of duodenum. Her contrast-enhanced computed tomography revealed mottled appearance in first part of duodenum, which is nonmobile in subsequent images suggestive of gossypiboma. A final diagnosis of gossypiboma with partial migration of gauge into duodenal lumen was made. Endoscopic removal was not attempted in view of possible risk of perforation and patient shifted to the department of surgery for further management.
Keywords: dyspepsia; endoscopy; foreign body; gossypiboma; pain abdomen